Gender Inequality in the Educational Environment: International Experience and the Republic of Kazakhstan (International relations and international law Journal, 2023)
Gender inequality in education has changed significantly over the past decades. After all, education is the most important tool for human resource development and a universal human right, as well as an important component of women's empowerment.This study attempts to answer the question: what changes have occurred in the field of gender inequality in the international educational environment through the analysis of domestic and foreign literature on this topic. The article deals with empirical research and theoretical views on gender inequality in the education system. It explores how education reform during the last decade affected on gender equality. An analysis of the trend of gender inequality in the world was also carried out. It explains the reasons of man and woman inequality in education and analyzes how it affects the economy, demography, social sphere, and so on.Thus, gender inequality in education has a direct impact on economic growth by reducing the average quality of human capital. It impedes progress in reducing fertility and infant mortality, thereby jeopardizing progress in welfare in developing countries. While this disparity is undesirable from a social equity perspective, it can also be argued that better use of women's potential in the marketplace can lead to greater efficiency. Education reproduces rather than challenges social inequalities. In addition, in some areas of relationships related to employment, education is important. This suggests that different interests can shape effect of schooling on men's attitudes towards women, and that education can offer women resources that encourage some change in their interpretation of status.Key words: inequality, education, gender, human resource, analysis.